2009
DOI: 10.1021/jm8014298
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cambinol Analogs as Sirtuin Inhibitors: Synthesis, Biological Evaluation, and Rationalization of Activity

Abstract: The tenovins and cambinol are two classes of sirtuin inhibitor that exhibit antitumor activity in preclinical models. This report describes modifications to the core structure of cambinol, in particular by incorporation of substitutents at the N1-position, which lead to increased potency and modified selectivity. These improvements have been rationalized using molecular modeling techniques. The expected functional selectivity in cells was also observed for both a SIRT1 and a SIRT2 selective analog.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(85 citation statements)
references
References 32 publications
6
79
0
Order By: Relevance
“…We first validated the compounds using an in vitro SIRT1 assay. We observed that while NAM, EX-527 and SIRT1 inhibitor IV displayed robust inhibition of SIRT1 in vitro, tenovin-6 had a weaker effect (consistent with its higher IC 50 ), 44,45 and HR73 42 had no effect under the conditions used (Fig. 2B).…”
Section: Resultssupporting
confidence: 60%
“…We first validated the compounds using an in vitro SIRT1 assay. We observed that while NAM, EX-527 and SIRT1 inhibitor IV displayed robust inhibition of SIRT1 in vitro, tenovin-6 had a weaker effect (consistent with its higher IC 50 ), 44,45 and HR73 42 had no effect under the conditions used (Fig. 2B).…”
Section: Resultssupporting
confidence: 60%
“…Compounds 7-9 were prepared by following reported procedures. [25,28,29] Finally, a further simplification of the tetracyclic scaffold of 5 was obtained by removal of the pyrimidinedione portion; thus the 2-benzoyl-1,2-dihydrobenzo[f]chromen-3-one 10 [30] (Figure 1) was prepared, which is also structurally related to other benzochromene-containing SIRT inhibitors such as splitomicin [31,32] and HR-73. [33] The new simplified analogues of 5, compounds 7-10, were tested at 50 mm against hrSIRT1 and hrSIRT2.…”
mentioning
confidence: 99%
“…High-throughput screening and rational design studies have found a large number of potent sirtuin inhibitors. Tenovins, MC2141, and EX-527 are SIRT1-specific inhibitors with an IC50 in the submicromolar range [48][49][50]. In addition, the most advanced SIRT1 inhibitor compound is selisistat (also known as EX-527 or SEN196), and it is being studied in a phase II clinical trial in Huntington's disease patients (see the Siena Biotech website) [50,51].…”
Section: Essential Characteristics Of Sirt1mentioning
confidence: 99%